PENGARUH PERSEPSI KEMUDAHAN, PERSEPSI KEBERMANFAATAN DAN PERSEPSI KEPERCAYAAN TERHADAP MINAT MENGGUNAKAN E-COMPLAINT (Studi kasus pada Mahasiswa Universitas Brawijaya) - Fajrina, Nur Syamsan (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2018)
This study aims to determine the effect of perceived ease of use, perceived usefulness and perceived trust to intention to use e-complaint. The research was conducted qualitatively with survey approach. Sample this study was students of Universitas of Brawijaya force 2012 until 2016 who have used e-complaint which amounted to 98 people. Data were analyzed by multiple linear regression analysis. The results showed that the perceived ease of use had a significant and positive influence on the intention to use e-complaint. Perceived usefulness had a significant and positive influence on intention to use e-complaint. Perceived trust had a significant and positive influence on intention to use e-complaint.Keywords: ease of use, usefulness, trust, intention to use